2011
DOI: 10.1002/cvde.201006898
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of ZnO Films from Bis(Ketoiminato)Zn(II) Precursors: Structure, Morphology and Optical Properties

Abstract: Two closely related bis(ketoiminato) zinc precursors, which are air stable and possess favorable properties for metal-organic (MO)CVD, are successfully employed for the growth of ZnO films on silicon and borosilicate glass substrates at temperatures between 400 and 700°C. The as-deposited films are investigated by X-ray diffraction (XRD), field emission scanning electron\ud microscopy (FESEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), nuclear reaction analysis\ud (NRA), as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 48 publications
7
26
0
Order By: Relevance
“…Additionally, a second order non linear emission related with previous phenomena was observed at 760 nm. Finally, a broad peak centered at around 510 nm (FWHM 100 nm) which could be associated to several mechanisms related with the structure of ZnO, including transitions between singly ionized oxygen vacancies and photoexcited holes, surface defects, among others, as announced and previously observed in other reports [17][18][19] . Interestingly, these emissions in the visible region are not dependent on the morphology of the ZnO.…”
Section: Band Gap Determination Using the Kubelkamunk Methodssupporting
confidence: 69%
“…Additionally, a second order non linear emission related with previous phenomena was observed at 760 nm. Finally, a broad peak centered at around 510 nm (FWHM 100 nm) which could be associated to several mechanisms related with the structure of ZnO, including transitions between singly ionized oxygen vacancies and photoexcited holes, surface defects, among others, as announced and previously observed in other reports [17][18][19] . Interestingly, these emissions in the visible region are not dependent on the morphology of the ZnO.…”
Section: Band Gap Determination Using the Kubelkamunk Methodssupporting
confidence: 69%
“…The resulting metal complexes could be promising candidates which potentially fulfill the criteria of volatility, suitable reactivity and sufficient thermal stability ( Scheme ) for atomic layer deposition and sufficient temperature window between volatilization and decomposition for low‐temperature CVD applications. Metal ketoiminates have been considered and applied as precursors for the CVD of metal oxides and nitrides of various transition metals, e.g., Ru, Ta, Nb, Zn, Pd, Cu, Ni, Ir, Ti . So far, none of these compounds have been tested for ALD applications, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, this peak is most probably assigned to V O . Firstly, Bekermann et al 37 have reported that the component of O-1s peak induced by outer atmosphere disappears to noise level after corroded by Ar þ . Inspired by this study, the O-1s spectra before and after Ar þ corroding are compared.…”
Section: Resultsmentioning
confidence: 99%